2021
DOI: 10.1002/hbm.25530
|View full text |Cite
|
Sign up to set email alerts
|

Proactive inhibition is not modified by deep brain stimulation for Parkinson's disease: An electrical neuroimaging study

Abstract: In predictable contexts, motor inhibitory control can be deployed before the actual need for response suppression. The brain functional underpinnings of proactive inhibition, and notably the role of basal ganglia, are not entirely identified. We investigated the effects of deep brain stimulation of the subthalamic nucleus or internal globus pallidus on proactive inhibition in patients with Parkinson's disease. They completed a cued go/no-go proactive inhibition task ON and (unilateral) OFF stimulation while EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…In contrast, the antisaccade task relies on proactive and selective response inhibition prior to the initiation of the selected response. In line with our findings, the notion that STN-DBS may differentially modulate reactive and proactive, respectively general and selective aspects of response inhibition has previously been discussed ( Obeso et al, 2013 , De Pretto et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the antisaccade task relies on proactive and selective response inhibition prior to the initiation of the selected response. In line with our findings, the notion that STN-DBS may differentially modulate reactive and proactive, respectively general and selective aspects of response inhibition has previously been discussed ( Obeso et al, 2013 , De Pretto et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…For example, beta band power over the right prefrontal cortex was higher during a stop signal task with DBS switched on compared to off-DBS state which was accompanied by improved response inhibition (Swann et al, 2011). Another recent EEG study found neither effects of STN-DBS on proactive response inhibition nor on the activity of the underlying cortical network compared to a nonoperated PD group (De Pretto et al, 2021).…”
Section: Effects Of Deep Brain Stimulation On Response Inhibitionmentioning
confidence: 97%
“…Bilateral STN-DBS also improves the proficiency of inhibiting upper limb movements measured with the Simon task [ 40 ], but the analysis of the EMG activity suggests that STN-DBS may weaken the suppression of the erroneous muscle activity [ 41 ]. Interestingly, unilateral STN-DBS does not affect inhibitory control of upper limb movements [ 42 , 43 ]. In contrast, DBS of the STN has been shown to result in increased errors on the Stroop interference task suggesting that stimulation may adversely affect the ability to suppress habitual prepotent responses [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%